THE INFLUENCE OF TRAINING, MOTIVATION AND COMPENSATION AGAINST EMPLOYEE PERFORMANCE ON PROCUREMENT CENTER AT DKI JAKARTA - Siti Mukhlidah; Nur Aktif (Dinasti International Journal of Education Management And Social Science, 2020)
This research aims to discover and examine those influence from training, motivation and compensation towards employee performance at DKI Jakarta's Procurement Center Agency. This research method used quantitative research by causality research. The population from this research were all employee at DKI Jakarta's Procurement center with amounted of 140 people. Sample chosen through saturated sampling method. Data collection method occured by questionnaires and interviews. Data processing using SPSS Windows 25.0 software with descriptive analysis and hypothesis test to multiple linear regression analysis. The results showed that: (1) Training variable partially had positive and significant impact to employee performance at DKI Jakarta's procurement center; (2) motivation variable partially had positive and significant towards employee performance at DKI Jakarta's Procurement Center Agency; (3) Compensation variable partially had positive and significant impact to employee performance at DKI Jakarta's Procurement Center Agency; (4) There had simultaneously significant impact between each variables of training, motivation and compensation towards Employee performance at DKI Jakarta's Procurement Center Agency.